Advanced multimedia and ubiquitous engineering MUE-FutureTech 2020 - Park, James J.; Loia, Vincenzo; Pan, Yi; Sung, Yunsick (Lecture notes in electrical engineering, 2021)
This book comprises selected papers from the 14th International Conference on Multimedia and Ubiquitous Engineering (MUE 2020) and the 14th International Conference on Future Information Technology (Future Tech 2020). And this book presents the latest developments in the field of ubiquitous computing technologies. It also discusses the state of the art in the development of computational methods, involving theory, algorithms, numerical simulation, error and uncertainty analysis, and novel applications of new processing techniques in engineering, science, and other disciplines related to ubiquitous computing. This book is a great resource for students, researchers, and professors working in the field of ubiquitous computing.